The transformation of American sex education : Mary Calderone and the fight for sexual health - More, Ellen Singer, 1946- (NYU Press, 2021)
"This book examines Americans' attempts to come to terms with the vexed subject of sex education in the schools from the late 1940s to the early 21st century. Using Mary Calderone's life and career as a touchstone, it traces the origins of modern sex education in the United States from the work of a group of reformers who coalesced around Calderone to create SIECUS in 1964 through the development and use of the competing approaches known as "abstinence-based" and "comprehensive" sex education from the 1980s into the 21st century"--